Obesity: The Role Dentists Play in Reducing the Prevalence of Obesity in Children, Adolescents, and Adults - Fadra Whyte; Kelly Motadel; Melissa Campos (Journal of the California Dental Association)
Read this article and take a quiz on the CDA online learning platform to earn 0.5 continuing education credit: www.cdapresents360.com/learn/catalog/view/20The practice worksheet is available online: https://doi.org/10.1080/19424396.2025.2514979